Frequency and predictors of individual treatment outcomes (response, remission, exacerbation, and relapse) in clinical adolescents with nonsuicidal self-injury - Reichl, Corinna; Rockstroh, Franziska; Lerch, Stefan; Fischer-Waldschmidt, Gloria; Koenig, Julian; Kaess, Michael (Psychological medicine, 2023)
BackgroundNonsuicidal self-injury (NSSI) is prevalent in adolescent clinical samples. There is evidence that NSSI can be treated effectively but data on individual treatment outcomes is limited. The goal of this study was to examine response, remission, exacerbation, and relapse rates over one and two years, respectively, among a clinical sample of adolescents with NSSI. Furthermore, we aimed to identify clinically relevant predictors of NSSI trajectories.MethodsThe sample consists of n = 203 adolescents (12-17 y., 94% female) from a specialized outpatient clinic for risk-taking and self-harming behavior with NSSI on at least five days in the six months before first assessment. Assessments were completed at baseline and one (FU1) and two (FU2) years later using structured clinical interviews and self-report questionnaires.ResultsAt FU1, 75% reported a reduction in NSSI frequency by at least 50% (treatment response); among those, one third (25% of the entire sample) achieved a remission (0 NSSI); an exacerbation (⩾50% more NSSI) was observed in 11% of patients. Of those in remission, 41% relapsed one year later. Predictors of non-response or non-remission were inpatient treatment and depressive symptoms. Adolescents with lower NSSI frequency at baseline had a higher risk of exacerbation. Due to limited sample size at FU2 no prediction model for relapse was established.ConclusionsWhile most adolescents presenting with NSSI achieved significant improvement, more attention should be paid to the rather low rates of full remission. Prediction and early detection of individuals who deteriorate during or relapse after treatment is critical.
Online veröffentlicht: 7. Juni 2023
Gesehen am 09.12.2024